Gambaran Sosiodemografi, Kebiasaan Merokok, Asupan Zat Gizi, Dan Status Gizi Pada Pasien Hipertensi Di Puskesmas Kecamatan Kramat Jati, Jakarta Timur: Sociodemographic Description, Smoking Habits, Nutritional Intake, And Nutritional Status Hypertention Patients At The Puskesmas Working Area Of Kramat Jati District, East Jakarta - Anggraini, Katrin; Khasanah, Tri Ardianti; Afrizal, Sandra Hakim (Program Studi Gizi, Fakultas Kesehatan Masyarakat, Universitas Binawan, 2024)
The prevalence of hypertension in people aged ≥ 18 years has increased in 2018. The research aims to describe the sociodemographic features, smoking habits and food intake in hypertensive patients. This type of research is descriptive with cross sectional involving 64 respondents with purposive sampling, the research was conducted in February 2023 at the Kramat Jati District Work Area Health Center. Data collection on weight, height, characteristics questionnaire, smoking habits and food intake. The results of this study were that the highest blood pressure was hypertension stage 1 (70.3%), age 56-65 years (62.5%), female gender (62.5%), high school education (45.3%), not working (62.5%), income ≤ (75.0%), never smoked (59.4%). excessive energy intake (46.9%), sufficient protein intake (54.7%), excessive fat intake (57.8%), sufficient carbohydrate intake (69.8%), overweight (48.4%). In conclusion, hypertensive patients are in the late elderly age group, female, have a high school education, do not work, have a low income, do not have a smoking habit, have sufficient energy intake, sufficient protein intake, high fat intake, and sufficient carbohydrate intake.